2019
DOI: 10.4097/kja.d.18.00322
|View full text |Cite
|
Sign up to set email alerts
|

Korean clinical practice guideline for perioperative red blood cell transfusion from Korean Society of Anesthesiologists

Abstract: Background Considering the functional role of red blood cells (RBC) in maintaining oxygen supply to tissues, RBC transfusion can be a life-saving intervention in situations of severe bleeding or anemia. RBC transfusion is often inevitable to address intraoperative massive bleeding; it is a key component in safe perioperative patient management. Unlike general medical resources, packed RBCs (pRBCs) have limited availability because their supply relies entirely on voluntary donations. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 104 publications
0
18
0
2
Order By: Relevance
“…For this reason, the application of viscoelastic coagulation test for liver transplantation can reduce bleeding and blood transfusion. Therefore, the Korean guideline for perioperative blood transfusion [ 28 ] and the guideline by the American Society of Anesthesiologists [ 29 ] consider the blood transfusion strategies using TEG and ROTEM to be important for not only liver transplantation but also perioperative blood management. Moreover, the guidelines for management of severe perioperative bleeding published by the European Society of Anaesthesiology [ 30 ] state that CCT is not suitable for surgeries in patients with liver disease and recommend TEG or ROTEM to diagnose perioperative coagulation disorders.…”
Section: Necessity and Advantages Of Viscoelastic Coagulation Test Fomentioning
confidence: 99%
“…For this reason, the application of viscoelastic coagulation test for liver transplantation can reduce bleeding and blood transfusion. Therefore, the Korean guideline for perioperative blood transfusion [ 28 ] and the guideline by the American Society of Anesthesiologists [ 29 ] consider the blood transfusion strategies using TEG and ROTEM to be important for not only liver transplantation but also perioperative blood management. Moreover, the guidelines for management of severe perioperative bleeding published by the European Society of Anaesthesiology [ 30 ] state that CCT is not suitable for surgeries in patients with liver disease and recommend TEG or ROTEM to diagnose perioperative coagulation disorders.…”
Section: Necessity and Advantages Of Viscoelastic Coagulation Test Fomentioning
confidence: 99%
“…Iron deficiency, secondary to intraoperative blood loss and increased iron requirements, is the leading cause of anaemia in surgical patients 3,4 . Identification of preoperative anaemia and iron deficiency has been recommended for all those with anticipated moderate to high (> 500 mL) surgical blood loss 5,6 .…”
mentioning
confidence: 99%
“…Factors that may influence the immunomodulatory effect of transfusions, including storage time 37 and use of leukocyte-reduced blood, 38 were not obtained. We note that South Korea does not mandate leukocyte depletion, 39 and in fact, one study found that only 10.3% of blood products in South Korea were leukocyte reduced in 2009. 40 The recency of our data had the disadvantage of limiting the possible follow-up period to 8 years, and any longer-term effects of transfusions were unable to be evaluated.…”
Section: Discussionmentioning
confidence: 73%